Reaction kinetics of in-situ methanolysis of Jatropha curcas seeds - Prabaningrum, N. (Trans Tech Publications Ltd, 2014)
In-situ methanolysis of Jatropha curcas had been investigated at various reaction temperatures along with reaction time. Increasing reaction temperature enhanced the yield of biodiesel and shortened the reaction completion. According to shrinking core model, the mechanism of in-situ methanolysis of Jatropha curcas was chemical reaction control with the first-order reaction. The constant of the first-order reaction rate in the range of 5.15Ã10-9 to 8.78Ã10-9 mÂ·s-1 and Arrhenius activation energy of 22.66 kJÃmol-1 were obtained. Â© 2014 Trans Tech Publications, Switzerland.